ANALISIS PDRB SEKTOR INDUSTRI DENGAN PENDEKATAN REGRESI SPASIAL: STUDI KASUS INDONESIA 2011-2015 - Defi Nofitasari; Teguh Hadi Priyono; Lilis Yuliati (Trunojoyo University of Madura, 2018)
Spatial analysis of econometric GRDP of industrial sector is one of regional econometrics study in an effort to define economic phenomenon which many developed by economic theories into mathematical form. This study aims to determine whether there is spatial influence between provinces in Indonesia, and how the influence of labor and investment variables to GRDP of industry sector in Indonesia. This study uses panel data from 2011-2015 which averaged and then processed using Geoda software, and the selected model is Spatial Error Model (SEM). The result shows that there is spatial inter-provincial relation with negative direction, which means that if there is an increase of GRDP of industry in study area will decrease GRDP of industry in neighboring region. Labor variable has a significant positive effect on the GRDP of industry, which means that if there is an increase in manpower will increase the GRDP of industry. Investment variable has positive significant positive effect, which means that if there is an increase of investment it will increase the GRDP of industry. In brief, this research can help the government to establish policies on the industrial sector and other economic sectors by considering the spatial aspects.